African bat species distribution models and gridded IUCN expert maps - K Matthias B Herkt; Jakob Fahr (PANGAEA, 2017)
IUCN expert maps are increasingly used in macroecological research. However, IUCN maps have not been produced for this purpose. Macroecological insights based exclusively on this data type could hence be misleading. Here we compare for a large taxonomic group (bats) and an entire biogeographic realm (Africa) the species-specific discrepancies between IUCN maps and species distribution models (SDMs), which were designed to approximate the complete geographic range of species. We then examine the implications for a typical macroecological analysis aimed at identifying environmental correlates of species richness. Here we provide data supporting the above analyses.
Supplement to: Herkt, K Matthias B; Skidmore, Andrew K; Fahr, Jakob (2017): Macroecological conclusions based on IUCN expert maps: a call for caution. Global Ecology and Biogeography, 26(8), 930-941, https://doi.org/10.1111/geb.12601